Introducing a High Performance Mg-Based Multicomponent Alloy as an Alternative to Al-Alloys - Tun, Khin Sandar; Kumar, Amit; Gupta, Manoj (Frontiers in Materials, 2019)
In this study, the design and development of a new Mg-based multicomponent alloy (ρ_th= 2.33 g/cc; ρ_ex= 2.15 g/cc) has been presented which exhibits excellent mechanical properties in hot extruded condition. Mg80Al5Cu5Mn5Zn5 alloy was designed and synthesized using disintegrated melt deposition technique followed by hot extrusion. The alloy was designed in such a way that the concentration of each alloying element remained ≥ 5 at % with Mg (80 at %) as base metal. Significantly high hardness (196 HV) was realized in Mg80Al5Cu5Mn5Zn5 alloy. Compression results showed substantially high ultimate compressive strength (UCS) 616 MPa of this alloy with a reasonably high ductility of 16.9%. This alloy also exhibited superior combination of tensile strengths (TYS- 211 MPa, UTS- 318 MPa) and ductility (8.2%). Overall combination of hardness, tensile and compression properties showed the current new light weight alloy system as an alternative to most of the commercially used Al-based alloys.